Full mouth rehabilitation in anterior crossbite and posterior bite collapse patient – A case report - Lunardhi, Louisa Christy; Salim, Sherman; Laksono, Harry (Indonesian Journal of Prosthodontic, 2020)
Background: Esthetically and functionally successful full mouth rehabilitation requires careful attention and me-ticulous treatment planning. Successful restoration in a patient with anterior crossbite and a partially edentulous situation can be challenging especially when bilateral posterior segment teeth is missing. Combination restora-tion using attachment retained removable partial denture (RPD) and removable partial overdenture (RPO) is such kind of treatment modality in prosthodontics. Purpose: This study was to provide an overview of a case about full mouth rehabilitation in anterior crossbite and posterior bite collapse patient. Case: A 64-year-old female pa-tient came to Prosthodontic Department of RSGMP Universitas Airlangga to have dentures replacing her missing teeth with aesthetic issue on her anterior teeth in order to eat well and be more confident. The patient wants to change her smile into new smile with acceptable aesthetic and function. Management: Diagnostic wax-up was made to capture the right occlusal vertical dimension (OVD) in centric relation (CR) that will be used in the first stage of full mouth rehabilitation, followed by management of the remaining teeth by endodontic and periodontal intervention by crown lengthening. Then, definitive restorations were made by maxillary attachment retained RPD with splint four anterior crowns and mandibular RPO with two single crowns on the lower teeth to correct anterior crossbite and posterior bite collapse. Conclusion: Patient had a satisfactoryly aesthetic and functional results with new occlusion using maxillary attachment retained RPD and mandibular RPO.